The intestines of the state : youth, violence, and belated histories in the Cameroon grassfields - Argenti, Nicolas (University of Chicago Press, 2007)
The young people of the Cameroon Grassfields have been subject to a long history of violence and political marginalization. For centuries the main victims of the slave trade, they became prime targets for forced labor campaigns under a series of colonial rulers. Today?s youth remain at the bottom of the fiercely hierarchical and polarized societies of the Grassfields, and it is their response to centuries of exploitation that Nicolas Argenti takes up in this absorbing and original book. Beginning his study with a political analysis of youth in the Grassfields from the eighteenth century to the.